The Dangerous Side of Social Media: Manipulating Bystander Aggression and Support to Cyberbullying Victims Through an Application of Side - (:unkn) unknown (My University, 2016)
Cyberbullying constitutes a complex social problem that is understudied among college students. A crucial factor contributing to the severity of cyberbullying is the level of bystander (un) involvement, or individuals who witness cyberbullying. A possible explanation for the different behaviors of bystanders is found in the theory of the Social Identity Model of Deindividuation Effects (SIDE), which suggests that CMC alters perceptions of the self and others. The current investigation (n = 442) employs an experimental design testing the SIDE model and predicted that individuals in more anonymous conditions would be more likely to adopt a disconfirming or a confirming group norm in the context of an online discussion group. A total of 442 college students participated in the study. Results suggest that the group norm significantly impacts how individuals respond to a cyberbullying victim. Implications of this result and information on the prevalence of cyberbullying in college are discussed. Suggestions for cyberbullying interventions based on these findings are offered.
Keywords: Bystanders; Computer-Mediated-Communication (CMC); Cyberbullying; Social Identity Model of Deindividuation Effects (side)